AB1273 TEACHING RARE DISEASES THROUGH ROLE PLAY: RESULTS OF AN EXPERIMENTAL WORKSHOP ON RAYNAUD PHENOMENON. (2nd June 2020) - Sanges, S.; Morell-Dubois, S.; Farhat, M. M.; Assaraf, M.; Lambert, M.; Sobanski, V.; Launay, D.; Hachlla, E.
Abstract : Background: Systemic autoimmune diseases are mostly taught through theoretical lectures, which do not allow for the acquisition of physical examination skills and semiologic confrontation. Objectives: We report herein the results of a pilot experiment using role-play to teach how to manage patients with Raynaud phenomenon (RP). Methods: We developed a workshop that consisted of two 30-minute OSCE (Objective and Structured Clinical Examination) stations. Students were divided into groups of 4 to 5 persons. On each station, 2 students were actors and 2 were observers. After a short briefing, students played a 15-minute scenario and then had a 15-minute debriefing. The first station simulated the case of a 26-year old woman referred for suspected RP. Students were instructed to perform clinical history taking and physical examination of the patient, formulated relevant diagnosis hypotheses and prescribe any additional necessary exams. Students had to suspect the diagnosis of idiopathic RP. The simulated patient was played by a trained facilitator with expertise on RP. The second station simulated the case of a 56-year-old woman referred for RP complicated by digital ulcers. Students received the same instructions as before. They had to suspect the diagnosis of systemic sclerosis. The patient role was held by a real patient with systemic sclerosis, followed by the physician who was supervising the station, who had received prior training and who agreed to participate in this training. At the end of the workshop, the students had to complete a satisfaction questionnaire. Results: A total of 21 students participated in the workshop and 17 completed the survey. The students were "very satisfied" (Likert 4/4) of this training in 94%. They considered this workshop "not very stressful" (Likert 2/4) and "very formative" (Likert 4/4) in 71%, but "a little short" (Likert 2/4) in 88%. After taking this training, all students felt "a little" (Likert 3/4, 24%) or "much more comfortable" (Likert 4/4, 76%) to manage patients with idiopathic RP; and "a little" (Likert 3/4, 65%) or "much more comfortable" (Likert 4/4, 35%) to manage patients with systemic sclerosis. All would recommend this workshop to other students. When asked about the strengths of this training, the students mentioned the benefits of being put in an immersive situation, which allowed for a better acquisition of practical skills (especially physical examination) and a more interactive exchange with teachers; as well as the confrontation with a real patient, which allowed for a better retention of semiologic findings and associated a relational component to this experience. The main weak points reported were its short duration and the stress induced by being observed during the simulation. Conclusion: This workshop suggests the interest and feasibility on a small group of students of a rare diseases awareness workshop using role-play. The evaluation of its pedagogical efficiency and its generalization on large student promotions are being considered. Acknowledgments: None Disclosure of Interests: Sebastien SANGES: None declared, Sandrine Morell-Dubois: None declared, Meryem-Maud Farhat: None declared, Morgane Assaraf: None declared, Marc Lambert: None declared, Vincent Sobanski: None declared, David Launay Grant/research support from: Dr. Launay reports personal fees from Actelion, grants and personal fees from Takeda, grants and personal fees from CSL Behring, outside the submitted work., Eric Hachlla: None declared